Analisis Faktor-Faktor yang Mempengaruhi Produksi Kelapa Sawit Rakyat di Desa Tebing Linggahara Kecamatan Bilah Barat Kabupaten Labuhanbatu - Siswanto, Yudi; Lubis, Zulkarnain; Akoeb, Erwin Nyak (Universitas Medan Area, 2020)
Palm oil has advantages compared to other vegetable oils such as coconut oil, soybean, or sunflower oil, its production per hectare is high, its economic life is long, and its use varies. This study aims to determine the effect of community palm oil production factors in the village of Tebing Linggahara, West Bilah District, Labuhanbatu Regency. The data used are primary data sourced from 176 oil palm farmers, by providing a questionnaire list. The research model is a quantitative model using multiple linear regression analysis techniques, using the SPSS version 16.0 program. The results showed that land area, seed, fertilizer, labor, plant age, and education level had an influence on palm oil production in Tebing Linggahara Village, West Bilah District, Labuhanbatu Regency, but other sources outside of oil palm farming had an effect on production palm oil for the people. The coefficient of determination R2 = 0.867 can be interpreted that oil palm production of 86.7% can be influenced by land area, seeds, fertilizer, labor, plant age, education level, and other sources outside of oil palm agriculture.